Migration responses to household income shocks: evidence from Kyrgyzstan - Kosec, Katrina (International Food Policy Research Institute, 2017)
Presented by Katrina Kosec (IFPRI), as part of the Annual Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 5-6 December 2017.